Pengaruh Pemberian Motivasi Dan Kepemimpinan Terhadap Semangat Kerja Karyawan Pada Hotel New Hollywood Pekanbaru - Anas Tasyana Silvi; Okta Karneli (Departement of Mathematics Education, 2023)
This research was conducted with the aim of knowing the effect of providing motivation and leadership on employee working spirit at the New Hollywood Hotel Pekanbaru. Providing motivation and leadership as independent variables (X1, X2) while employee working spirit as the dependent variable (Y). The problem that occurs in this study is the lack of employee working spirit at the New Hollywood Hotel Pekanbaru. This can be seen from the data on labor turnover and company attendance. The sample for this research was taken as many as 55 respondents from the population which was calculated using a census/total sampling. The data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS program. The data analysis technique used is validity and reliability test, multicollinearity classic assumption test, multicollinearity classic assumption test, heteroscedasticity classic assumption test, simple linear analysis, multiple linear analysis, coefficient of determination, t test and f test. Based on the results of the tests conducted, it shows that the provision of motivation and leadership has a positive and significant effect on employee working spirit at the New Hollywood Hotel Pekanbaru.